If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 15 + 5x = -1 Reorder the terms: 15 + 3x + 5x = -1 Combine like terms: 3x + 5x = 8x 15 + 8x = -1 Solving 15 + 8x = -1 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -15 + 8x = -1 + -15 Combine like terms: 15 + -15 = 0 0 + 8x = -1 + -15 8x = -1 + -15 Combine like terms: -1 + -15 = -16 8x = -16 Divide each side by '8'. x = -2 Simplifying x = -2
| 3d^2+7d-6=0 | | 2y=3y-15 | | -3n(4b)+2a(3b)= | | 10x-9=2x-69 | | 8(2x+1)=4x-6x | | 12-6x=5-3+15x | | -5x-5=-5x | | 3(2x-5)=-39 | | 14+2x=-9-5x+4x | | 7g=49 | | y=-1/4+1 | | 3(x+3)=8x+6-5x+3 | | 9-9x=173-37x | | -2/5= | | 3x-12=4x-9 | | 5(2-y)+7y=-3(y+5) | | 3x+8=116 | | -3x+5=-3x+4 | | -3*-4*4-4*-4*-2= | | x-8=-51 | | 4y-7=3-2(9y-15) | | -6x-33=-3x-27 | | .35x+.20(240-x)=57 | | -3x-25=4(x-1) | | 8x^3-20x^2-2x+5=0 | | -6=-3+x | | 2x+6=9+3x-3 | | 8x^3-20x-2x+5=0 | | .4x+4.2=.3x+2.6 | | (2x-9)+14=(3x-8) | | 7X=10X | | 12=2(x+1)-6 |